The MHC and MHC molecules 2 - Kaufman, Jim (Henry Stewart Talks, 2022)
Genetics, nomenclature, polymorphism, and function of MHC molecules, Mouse genetics is largely based on inbred strains, Transplantation and T cell selection in the thymus, Autoimmunity, allergy, and immunopathology, MHC and mate choice and reproduction, MHC-determined pathogen and infectious disease resistance